SOSIALISASI SASTRA ANAK SEBAGAI SUMBER BAHAN AJAR DALAM PENDIDIKAN KARAKTER PADA TINGKAT SEKOLAH DASAR - Wulandari, Sovia (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Public and private elementary schools in Jambi city have not implemented children's literature-based teaching materials for character education. Character education has so far only relied on learning Religious Education. Therefore, elementary school teachers need to be given knowledge about children's literature, moral values in children's literature, and how to make teaching materials based on children's literature, as well as how to apply these teaching materials at school so that they can be understood and applied by elementary school students in their daily lives. The method used in this service activity is socialization and training in making teaching materials based on children's literature. The results obtained from this service activity were 74 teachers who participated in socialization activities and 46 teachers participated in training activities. All teachers who participated in the training were able to make teaching materials sourced from children's literature for character education in elementary schools as shown by the teaching materials they had made. The teaching materials that have been made by these teachers have been collected in the form of an ISBN book.